1994
DOI: 10.1021/ac00090a025
|View full text |Cite
|
Sign up to set email alerts
|

Automated Analysis of Trace Metals by Flame Atomic Absorption Spectrometry

Abstract: This paper describes implementation of instrument control and data analysis software for fully automated, unattended analysis of metals by flame atomic absorption spectrometry (FAAS). Error trapping and correction are an essential part of the software system if an automated instrument is to run unattended. The design and implementation of two programs, AA-Quality Control (AA-QC) and AAcontrol, that form part of the expert system AAexpert are described. AAcontrol carries out instrument control, automated sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1995
1995
1997
1997

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…32-34-43 AAcontrol is a prototype concerned with the automation of the flame AAS analysis process. 44 We have found that knowledge acquisition is most effective when it is focused on particular cases rather than on the entire target domain. Such cases involve relatively narrow, more specific, and, therefore, less complex problem subdomains.…”
Section: Computing Environmentmentioning
confidence: 86%
“…32-34-43 AAcontrol is a prototype concerned with the automation of the flame AAS analysis process. 44 We have found that knowledge acquisition is most effective when it is focused on particular cases rather than on the entire target domain. Such cases involve relatively narrow, more specific, and, therefore, less complex problem subdomains.…”
Section: Computing Environmentmentioning
confidence: 86%
“…A calibration graph was obtained in under 1 min, and it was also shown how a standard additions method of calibration could be performed. Instrument control and data analysis software was described (265) for routine analysis by FAAS. Included was an expert system for detection of errors during unattended operation.…”
Section: Flame Atomic Absorption and Emissionmentioning
confidence: 99%
“…99,156,157 The AAexpert program has been designed to implement totally automated analysis by flame AAS. 100 PAWMI is a program developed to carry out automated identification of bulk organic waste mixtures using IR data as a preliminary screening tool prior to quantitative analysis. 102 A number of instrumental diagnostic expert systems have been developed.…”
Section: Expert System Applications In the Chemistry Domainmentioning
confidence: 99%
“…For nearly 20 years, our laboratory has been involved in the application of computer technology in instrumental analysis. 100,[109][110][111]119,126,136,[141][142][143][144][145][146][147][148][149] The early work, programs such as CDSCAN, SpectraManager, and Simpfit, were computer programs developed specifically for instrument control and manipulation of spectral data using the concept of spreadsheets. [142][143][144][145] These programs dealt with problems that are more procedurally and numerically oriented and common in experimental spectroscopic research.…”
Section: Applications In Analytical Chemistrysthe Acexpert Projectmentioning
confidence: 99%
See 1 more Smart Citation